Comparative study of doped and doping less charge plasma silicon microstrip detector. (2023) - Kumar, Rakesh; Kumar, Jitendra; Beloni Devi, L.; Singh, Kundan
Abstract: Microstrip silicon detectors are one of the key trackers in particle physics experiment like LHC at CERN. There is a continuous need to improve upon various parameters of detectors like breakdown voltage, leakage current, full depletion voltage, post radiation hardness, charge collection efficiency and low thermal budget. We have introduced new doping less silicon microstrip detector for the very first time and investigated the various parameter of the detector. We have studied and compared the results of doped and dopingless charge plasma silicon microstrip detector. Our study shows improvement in Preradiation breakdown voltage of 2200 V with leakage current of 5.2 pA/um in dopingless charge plasma microstrip detector as compared to 1500 V of breakdown voltage with leakage current of 6.5pA/um as in the case of doped silicon microstrip detector.